Expression, purification and enzyme activity definition of soybean epoxide hydrolase mutants at Asp 101 (D101) position - Minh, Nghiêm Ngọc; Fukazawa, Chikafusa (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 73-78, 2005